Examining and classifying key factors influencing teachers' creativity in integrating Information and communication technologies in education - Karim Lkamel; Jalal Assermouh (Кардиоваскулярная терапия и профилактика)
This study explores how teachers' socio-demographic characteristics influence their creativity in classroom integration of Information and communication technology (ICT). Using a quantitative, exploratory methodological approach involving 110 teachers, we examined factors such as age, gender, education level, and teaching experience in relation to ICT use. multiple correspondence analysis was employed to develop a typology of innovative teachers based on these socio-demographic factors and their degree of ICT integration. Furthermore, multiple linear regression analysis revealed that socio-demographic characteristics significantly correlate with ICT use. Our final model, incorporating four independent variables — age, experience, university degree, and gender — explains 42% of the variance in teachers' ICT integration, a considerable level of explanatory power. These findings offer valuable insights for designing educational policies and professional development programs aimed at fostering creativity in ICT use, tailored to the socio-demographic profiles of teachers.